(untitled) (Tri-Chandra Journal of Anthropology, 2025)
This paper explores how the discourse of sexual purity (satitwa) is constructed in the Hindu epic Ramayana as a mechanism for regulating female subjectivity. In the Hindu social system, controlling female sexuality is not merely a matter of personal virtue but is deeply tied to maintaining familial harmony, preserving caste lineage, and fulfilling spiritual ideals such as purity and liberation. For centuries, Hindu norms have mandated that women bear the same bloodline as their husbands and undergo prescribed samskāras and rituals to ensure social order. Within this framework, a husband’s role extends beyond physical protection to guarding his wife’s sexual integrity, thereby safeguarding the moral and genealogical legitimacy of the family. The Ramayana exemplifies this sexual grounding of social order, where any suspicion regarding a woman’s chastity invites scrutiny, trials, and public judgment. By employing Foucauldian discourse analysis, this paper critically examines how satitwa is discursively produced and how violence against Sita becomes justified as a necessary act to reassert male authority and affirm the husband’s role as the ‘protector of truth.’ Conceptually, the study argues that the discourse of sexual purity in the epic internalizes power, diffuses it into everyday life, and legitimizes structural violence under the guise of dharma. Theoretically, the paper challenges conventional gender relations in Hindu society and seeks to interrogate the normalized violence against women through the lens of contemporary feminist thought.